Character Education Based on Local Wisdom: A Study of the Sasak Tribe Community in Lombok - Muhirdan, Muhirdan; Hulaimi, Ahmad; Hidayanti, Nur Fitria; Ariani, Zaenafi; Hamdi, Hamdi; Wahyudi, Zaenul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the forms of character education based on the local wisdom of the Sasak community and their role in character formation in everyday life. The research used a qualitative, ethnographic design and was conducted in Sade Village, Rembitan, and Segenter, all of which are Sasak customary communities. The data were collected through participant observation, in-depth interviews, and documentation, and were then analyzed using an interactive model. Data validity was examined through source triangulation, technique triangulation, and member checking. The study's results show that character education in the Sasak community is internalized through four main domains. First, religious values, manifested through Quran recitation activities, village religious gatherings, and the tradition of ngaji menaq, serve as the foundation for character formation derived from the local wisdom of the Sasak community. Second, local wisdom instills values of prudence, honesty, and moral responsibility. Third, the practice of gotong royong (besiru, begawe, mandek bale) strengthens prosocial character, which is perceived as good character in social relations. Fourth, Tuan Guru and traditional leaders play a central role in character education through role modeling, advice, and the transmission of adat-pamali values integrated with Islamic sharia. The research findings affirm that character education in the Sasak community occurs through concrete, continuous cultural processes. Overall, this study shows that Sasak local wisdom makes a strategic contribution to the development of religious, ethical, and prosocial character aligned with its principles on the island of Lombok